Protective effect of Dapagliflozin against Amphotericin B-induced nephrotoxicity in an experimental rat model - Akburak, Ercan; Kaya, Bülent; Tan, Seyhmus; Avci, Cagri; Eren Ates, Kivilcim; Gonlusen, Gulfiliz; Sapmaz, Tugce; Mete, Burak (Scientific Reports in Medicine, 2025)
Objective: Background: Amphotericin B deoxycholate (AmBD), a potent antifungal agent, is limited by significant nephrotoxicity. SGLT-2 inhibitors, such as dapagliflozin, exhibit renoprotective effects beyond glycemic control. This study aimed to investigate the potential protective effects of dapagliflozin against AmBD-induced nephrotoxicity in an experimental rat model.Materials and Methods: Thirty-two Wistar albino rats were randomized into four groups (n=8): Control, AmBD (single 50 mg/kg i.p. dose), Dapagliflozin (10 mg/kg/day, gavage), and AmBD + Dapagliflozin. After seven days, serum levels of creatinine, BUN, oxidative stress markers (TOS, MDA, MPO), antioxidant enzymes (CAT, SOD, GPx), and apoptotic mediators (Bax, Bcl-2, Caspase-3) were analyzed. Renal tissues were evaluated for histopathological changes.Results: AmBD administration induced significant acute kidney injury, characterized by elevated serum BUN and creatinine levels and severe histopathological damage, including tubular necrosis and dilatation. Co‑administration of dapagliflozin significantly attenuated these functional and structural injuries, but its effect on systemic oxidative stress and apoptotic markers could not be demonstrated in this model.Conclusion: Dapagliflozin partially prevented AmBD-induced elevations in BUN and creatinine and significantly ameliorated histopathological damage. However, no significant effect was observed on systemic oxidative stress or apoptotic markers in this model